2015
DOI: 10.1021/acs.macromol.5b00931
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Versatile and Tunable Nanostructuration of Ionic Liquids on Fluorinated Copolymer

Abstract: International audienceA fundamental understanding of the versatile and tunable nanostructuration effect of two phosphonium ionic liquids (ILs), denoted octadecyltriphenylphosphonium iodide (IL-C18) and tributyl(methyl)phosphonium methylsulfate (IL-108), on a semicrystalline fluorinated copolymer poly(vinylidene fluoride-co-chlorotrifluoroethylene) (P(VDF-CTFE)) was elaborated. This research suggests that the nanostructuration mechanism is very dependent on the diffusion and interacting abilities of ILs in matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 55 publications
(106 reference statements)
2
48
0
Order By: Relevance
“…Then, combining the FTIR data with the X‐ray diffraction (XRD) spectra, it can be concluded that a very high content of β phase is obtained for the electrospun PVDF nanofibers. In fact, the presence of diffraction peaks at 20.7° (200/110) and 36.6° (101) suggesting that the use of electrospinning process induces the all‐trans β crystal conformation . Nevertheless, despite the decrease of the diffraction peak at 18.6° (002) of the electrospun fibers, the α phase is always present.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Then, combining the FTIR data with the X‐ray diffraction (XRD) spectra, it can be concluded that a very high content of β phase is obtained for the electrospun PVDF nanofibers. In fact, the presence of diffraction peaks at 20.7° (200/110) and 36.6° (101) suggesting that the use of electrospinning process induces the all‐trans β crystal conformation . Nevertheless, despite the decrease of the diffraction peak at 18.6° (002) of the electrospun fibers, the α phase is always present.…”
Section: Resultssupporting
confidence: 89%
“…In addition, the absorption intensity of the band at 840 cm −1 significantly increases with the increase of the fibers orientation. According to the literature from Yang et al, this band corresponds to the absorbance of trans segments longer than TT, suggesting that nonpolar α phase is converted to polar β phase …”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In all the samples, two diffraction peaks were observed at 2θ = 17.9° and 20.0°, regardless of the solvent used. These peaks correspond to α‐crystal planes with Miller indices of (100) and (110), respectively, in PVDF‐ co ‐CTFE . When comparing the two solvents, the peak at 26.7°, which is assigned to the α (021) plane, was observed in only those membranes prepared with NMP.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, investigations on poly(vinylidene fluoride) (PVDF) modified by room temperature ionic liquids (ILs) have been widely reported in the literatures . The incorporation of ILs leads to the formation of electroactive phases ( β or γ phase) of PVDF . PVDF/IL blends have the potential applications as solid polymer electrolytes, actuators, biomedical devices, and smart materials .…”
Section: Introductionmentioning
confidence: 99%